THE EFFECTS OF INFLATION AND USD EXCHANGE RATE ON COMPANY RETURNS IN INDONESIA - Reginata Saharany Kustanti; Josephine Elliska Dinata (PT. Media Akademik Publisher, 2024)
This paper provides a comprehensive examination of the effects of inflation and USD exchange rate changes on company returns in Indonesia. It delves into the intricate relationship between these macroeconomic variables and their implications for corporate performance within the Indonesian context. The study reveals that inflation, as measured by the consumer price index (CPI), can stimulate economic growth while imposing cost pressures on businesses across various sectors. Additionally, fluctuations in the USD exchange rate significantly influence company returns, with export-oriented industries benefiting from a weaker IDR and import-dependent sectors facing challenges during currency appreciation. The tourism and hospitality sectors are highly sensitive to currency fluctuations, with a weaker IDR attracting more foreign tourists and boosting tourism revenues. Effective risk management strategies, including hedging against currency fluctuations and diversifying revenue streams, are essential for companies to mitigate the impact of inflation and exchange rate volatility on their profitability. Policymakers play a crucial role in maintaining exchange rate stability and implementing measures to support businesses affected by currency movements, ensuring sustainable economic growth and development in Indonesia.